Konsensualny charakter procedury jako konstytutywna cecha ADR - Duszka-Jakimko, Hanna; Haczkowska, Monika (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Consensual importance of the law is an increasingly emerging issue in contemporary reflection on law. Alternative legal dispute resolution with Alternative Dispute Resolution — ADR, which includes the basic methods of negotiation, mediation, conciliation and arbitration, is one of the manifestations of this thought. This article, highlighting the various methods of ADR, shows the importance of the consensual nature of the procedure as one of the constitutive conditions of the agreement which was the basis for legitimizing solutions in a legal dispute within the ADR. The article takes into account the Polish legal system, extracts and presents different criteria, such as subjective criteria, jurisdiction, the degree of formalization of procedures, grounds for jurisdiction, of the power and coercion, making references, comparatively, to the court procedures and ADR procedures. The wording of the above criteria allows to determine the ADR procedures as consensual procedures, based on the agreement of free, independent entities, as well as on certain values and conditioned by a legal culture.
Keywords: methods of ADR; civil procedure; criminal procedure; administrative procedure